Pengaruh Pemberian Formula Tepung Tempe sebagai Bahan Substitusi pada Formula Enteral Rendah Lemak (Hospital Made) Terhadap Kadar Ldl dan Hdl Darah Tikus (Rattus Novergicus) dengan Diet Aterogenik - Meirina S Loaloka; Maria Goreti Pantaleon (Program Studi Gizi, Universitas Bumigora, 2020)
Tempe flour is one of food material that contains high protein biovability value and high potential in preventing coronary heart disease by decreasing the cholesterol content. Tempe has hypocholesterol effect that able to inhibit the cholesterol absorption. Beside that, tempe contains strong antioxidant that able to protect LDL oxidation. The research aimed at knowing the influence of tempe flour giving as substitution material at low fat enteral formula (hospital made) toward the increase of LDL content and the decrease of HDL content at male rate of wistar norvegiccus strain that given atherogenic diet. The research was laboratory experimental in nature with complete design with 4 repetition for each treatment stages. The measured variables included independent variables, that is enteral formula giving at hospital that consist of 6 treatment stages, that is (Po) Standard diet, (P1) Atherogenic diet, (P2) Standard Diet + Hospital Enteral Formula, (P3) Standard Diet + Enteral formula of Tempe Flour Substitution, (P4) Atherogenic diet + Hospital Enteral Formula, (P5) Atherogenic Diet + Enteral formula of Tempe Flour Substitution and the dependent variables were LDL and HDL. The results showed that the highest cholesterol serum content in average at treatment group without tempe flour giving (P4) was 199±8.14; while the lowest at the treatment with tempe flour giving (P3) was 18.2±6.65. The highest HDL cholesterol serum content in average was 78.9±2.18 while the lowest at treatment (P1) Atheroganic Diet was 26.5±3.57. The statistical test showed there was significant content differences between LDL and HDL at teach treatment (P =0.000). The body weight measurement of he initial sample from all treatment was homogenous (P = 0.052), then after the treatment finished produced different body weight average (P =0.000), where the difference at the treatment group with tempe flour. Each intake of nutrient (energy, protein, fat, and carbohydrate) at all treatments have differences, that is (P =0.000) The conclusion of the research was the tempe flour with atherogenic diet able to decrease the LDL oxidation that showed by the LDL cholesterol serum and the high HDL content. The giving of the flour able to prevent the LDL cholesterol serum content, prevent the HDL cholesterol serum decrease and able to inhibit the rat body weight significantly.